Intervención de enfermería en pacientes sometidos a trasplante hepático en ecuador - Ramírez Cañaveral, Soraya Pamela (2025)
Liver transplantation is a complex procedure that requires specialized nursing interventions to optimize clinical outcomes and quality of life for patients. Worldwide, approximately 30,000 liver transplants are performed annually, with annual survival rates exceeding 85% in many specialized centers. In Ecuador, between the year 2022, 28 liver transplants were performed, a study conducted indicates an overall survival rate of 72% at 12 months’ post-transplant, with 17 of 62 patients transplanted. The aim of this study was to design a practical guide of nursing interventions for patients undergoing liver transplantation in Ecuador. A qualitative systematic review of the available scientific literature was conducted, following PRISMA guidelines, analyzing 14 relevant articles published between 2020 and 2024, which served as the basis for the creation of a comprehensive guide that covers all phases of liver transplantation, from preoperative assessment to long-term follow-up, including specific nursing interventions in post liver transplant patients such as postoperative monitoring, nutritional management, administration of immunosuppressants, prevention of complications and assessment of quality of life. The guidelines provide detailed guidelines adapted to the Ecuadorian context, filling an important gap in the existing literature and offering a practical-clinical instrument to improve nursing interventions in liver transplantation in Ecuador.